Hyaluronic Acid Accelerates VEGF and PDGF Release from Advance Platelet Rich Fibrin in Diabetic Foot Ulcer - Ronald Winardi Kartika; Idrus Alwi; Franciscus Dhyanagiri Suyatna; Ferry Sandra; Em Yunir; Sarwono Waspadji; Suzzana Immanuel; Todung Silalahi; Saleha Sungkar; Jusuf Rachmat; Saptawati Bardosono; Mirta Hediyati Reksodiputro (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Hyaluronic acid (HA) is an essential component of extracellular matrix and mediates signaling in wound healing. HA could induce growth factor release from Advanced Platelet Rich Fibrin (A-PRF), including Vascular Endothelial Growth Factor (VEGF) and Platelet-derived Growth Factor (PDGF). However, concentrations of the released-VEGF and PDGF have not been clearly disclosed. Therefore, current study was conducted to measure the release of these growth factors in HA + A-PRF gel of diabetic foot ulcer (DFU) subjects.METHODS: Twenty DFU subjects were included in the study and treated with A-PRF or HA+A-PRF. A-PRF was derived from autologous peripheral blood and processed with low-speed centrifugation. HA was added with a ratio of 1:0.6. A-PRF or HA + A-PRF was applied topically on DFU. Upper tips of A-PRF or HA + A-PRF gels were collected on day 0, 3 and 7 for measurements of VEGF and PDGF concentrations with Enzyme-linked Immune-sorbent Assay (ELISA) methods.RESULTS: On day-3, both VEGF and PDGF concentrations of HA + A-PRF group were significantly higher than the VEGF (p=0.000) and PDGF (p=0.019) concentrations of A-PRF group. The VEGF and PDGF concentrations were continuously and significantly increased on day-7 of HA + A-PRF group, compared to the VEGF (p=0.000) and PDGF (p=0.004) concentrations of A-PRF group.CONCLUSION: Combination HA+A-PRF induces VEGF and PDGF release from A-PRF. A mixture of A-PRF and HA could be more effective than A-PRF alone for treatment of DFU.KEYWORDS: hyaluronic acid, advanced platelet rich fibrin, PRF, growth factor, VEGF, PDGF, diabetic foot ulcer